CORRELATION BETWEEN KNOWLEDGE, ATTITUDE, AND COMPLIANCE WITH THE USE OF PERSONAL PROTECTIVE EQUIPMENT AMONG CLEANING SERVICE STAFF IN CITO LABORATORY - Nastiti, Herwin Rizky; Prihatiningsih, Diah; Andini, Ni Komang Sukra (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Cleaning service staff working in laboratories are at high risk of exposure to hazardous materials. The use of personal protective equipment (PPE) is a crucial step in preventing occupational accidents. However, the level of compliance with PPE usage varies and is influenced by the knowledge and attitude of the staff. This issue highlights the need to understand the relationship between the knowledge and attitudes of cleaning service staff and their compliance with the use of PPE. This study employed an analytical design with a cross-sectional approach. A total of 58 cleaning service staff participated as respondents, selected through total sampling. Data were collected using a structured questionnaire and analyzed using the chi-square test. The results showed that 60.3% of respondents had good knowledge regarding the use of PPE, while 73% had a positive attitude toward its usage. The chi-square test revealed a p-value of 0.03 (<0.05), indicating a significant relationship between attitude and compliance with PPE usage among cleaning service staff. The chi-square test for the relationship between knowledge and compliance yielded a p-value of 0.01 (<0.05), indicating a significant relationship between knowledge and compliance. The findings indicate that the knowledge of cleaning service staff positively correlates with their compliance in using PPE. Staff members with good knowledge were more likely to comply with PPE usage. Adequate knowledge enables staff to understand laboratory risks and the benefits of PPE in preventing exposure to hazardous materials, thereby encouraging safer behavior, promoting communication among staff, reminding one another, and embedding safety values into daily work routines.